LQG and fuzzy correction mechanism in tilting railway vehicle control design - Zamzuri, H. (2007)
This paper reveal the work on modern control approaches on titling railway vehicles. The design of the LQG with integral action will force the output to the steady state zero while by adding fuzzy mechanism to the controller will improve the performance of the system both for the deterministic and stochastic track. Moreover, the used of multiobjective GA as a tuning method seek an optimum values based to the constraints in the objective functions.